Problematika Implementasi Akad Bai` Bitsaman Ajil Perspektif Hukum Islam pada BMT Sidogiri Cabang Situbondo - Imam Nawawi Imam Nawawi; M. ZIDNY NAFI' HASBI ZIDNY NAFI' (ITB AAS INDONESIA Surakarta, 2021)
Abstract The shift in national economic policy that follows global economic developments has led the government to improve its economic activities. One of the economic activities that are improved is banking activities. The legal instrument that was improved was the issuance of Law No. 7 of 1992 on Banking. This research aims to analyze how the presence of sharia financial institutions such as BMT UGT (Integrated Joint Venture) Sidogiri is responded enthusiastically by Muslims who are the majority in Indonesia. The research method uses qualitative method with data collection techniques using observation methods, interviews, and research libraries to find sources and data that support this writing. Then from the data is analyzed using qualitative analysis methods that are based on doctrinal approaches and interpretations of the data sources obtained. Based on the results of the study can be known that the application of akad bai' bitsaman jail (BBA) in BMT UGT Sidogiri assemblages auxiliary branch is the inclusion of another contract namely wakalah agreement. Ada two models that are carried out, the first goods are still handed over to BMT by the customer who became a representative, only then handed back by BMT to the customer earlier. This is valid because BMT UGT sidogiri and nasabah have agreed to follow Islamic law and banking regulations. Second, the goods are immediately taken home by the customer and become property rights, without first being handed over to BMT. This method is legally invalid. After all, it is not following Islamic shari'a because it happened ittihadul quality wall muqbit